Competition policy - Cagney, Denis (Statistical and Social Inquiry Society of Ireland, 1994)
Competition policy can be a fascinating topic, particularly for those with an economic or legal frame of mind. This same intellectual fascination can also be a pitfall. One can easily be drawn into conceptual minefields when all a client wants to know is "Can I go ahead with this joint venture or is there some competition problem?" Or "Is my rival engaging in predatory pricing or is he staying within the rules of the game?" The list is endless. The last thing the client wants to hear is: "Well there are different schools of thought on this issue...."! Perhaps the single biggest challenge facing competition policy-makers is to enable business operate in a climate of reasonable certainty while developing a consistent body of rules on what can sometimes be very difficult questions. In Ireland, policy really only emerges through individual cases because of the Competition Act, 1991. This does not help matters. There will always be some uncertainty in living with the competition rules. But we should keep it to the minimum necessary.
Symposium on competition policy
Read before the Society, 3 March 1994
Keywords: Competition policy; European economic integration; 314.15